Factors associated with infant mortality in Nigeria: A scoping review. - Loveth Dumebi Nwanze; Alaa Siuliman; Nuha Ibrahim (PLoS ONE)
Background Infant mortality persists as a global public health concern, particularly in lower-middle-income countries (LIMCs) such as Nigeria. The risk of an infant dying before one year of age is estimated to be six times higher in Africa than in Europe. Nigeria recorded an infant mortality rate of 72.2 deaths per 1,000 live births in 2020, in contrast to the global estimate of 27.4 per 1,000 live births. Several studies have been undertaken to determine the factors influencing infant mortality. Objective This scoping review sought to identify and summarise the breadth of evidence available on factors associated with infant mortality in Nigeria. Methods This review followed the five-stage principles of Arksey and O'Malley's framework. Four electronic databases were searched with no limit to publication date or study type: Ovid MEDLINE, PubMed, CINAHL Complete, and Web of Science. Selected studies were imported into Endnote software and then exported to Rayyan software where duplicates were removed. Included articles were thematically analysed and synthesised using the socioecological model. Results A total of 8,139 references were compiled and screened. Forty-eight articles were included in the final review. At the individual level, maternal- and child-related factors were revealed to influence infant mortality; socioeconomic and sociocultural factors at the interpersonal level; provision and utilisation of health services, health workforce, hospital resources and access to health services at the organisational level; housing/neighbourhood and environmental factors at the community level; and lastly, governmental factors were found to affect infant mortality at the public policy level. Conclusion Factors related to the individual, interpersonal, organisational, community and public policy levels were associated with infant mortality in Nigeria.